Removal of acid from diesel by tetramethylammonium hydroxide/ethanol. (2nd May 2016) - Zhen, Hu; Hailian, Yu
ABSTRACT: Naphthenic acid was removed by tetramethylammonium hydroxide as deacidification agent from diesel, and ethanol was used as extractant. The effect of parameters in the deacidification process was investigated systematically. The process parameters included mass fraction of deacidification agent, volume ratio of deacidification agent to diesel, reaction time, reaction temperature, and resting time. On the basis of single-factor experiments, orthogonal experiments were done to optimize the deacidification process. The results showed that the optimum deacidification process was that mass fraction of deacidification agent was 3.5%, volume ratio of deacidification agent to diesel was 0.25, reaction time was 50 min, reaction temperature was 323 K, and resting time was 30 min. the acidity in diesel was reduced from 135.52 to 4.07 mgKOH/100 mL, and deacidification rate reached 97.0%.